Implementation of Mind Mapping Learning Model in Improving Student Learning Outcomes at Pesantren Al-Falah Wuluhan Jember Elementary School - Mashudi Mashudi; Depict Pristine Adi (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2024)
The problem in this study is that learning is dominated by the lecture method by teachers. The purpose of this research is to analyze the use of the mind mapping model in improving the learning outcomes of Islamic Religious Education in grade V students of SD Pesantren Al-Falah Wuluhan Jember. The use of the mind mapping model is very effective to come up with ideas and notes that students make to form a pattern of thinking with the topic and sub-topic of discussion and its branches. The mind mapping model prepares, first to determine learning objectives, second to compile learning tools using the mind mapping learning model, third to prepare cartons and color tools to make mind mapping, and fourth to make evaluation tools. After that, learning is by what you want to achieve or RPP. The research used is Class Action Research where the implementation of research is carried out in 2 cycles of Action treatment. Each cycle is carried out in the presence of planning and execution. The object of study was 22 students consisting of 10 men and 12 women. The results of the study stated that the treatment cycle began with a procyclical which obtained an average of 42.27 from 22 students. This condition was continued on Action Cycles 1 and 2 with an average gain of 64.55 and 85.77, respectively. From the three cyclical actions, the completeness of learning outcomes in cycle 1 was 36.36%, and in cycle 2 it was 77.27%. From the results of the study, it can be concluded that the use of the mind mapping model can improve student learning outcomes in Islamic Religious Education subjects with the subject matter Lesson 2 Knowing Allah and His Book.